Respon Ukuran Benih dan Benih yang Berasal dari Pemakaian Paclobutrazol terhadap Pertumbuhan dan Produksi Benih Kentang G4 (Solanum tuberosum) Varietas Granola - Agustina E Marpaung; Bina Karo; Susilawati Barus; Kuswandi Kuswandi (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2019)
The use of quality seeds increase productivity and competitive the success of a potato agribusiness. This study aims to determine the influence of seed size and seed origin paclobutrazol use of growth and production of potato seeds. The research conducted in Berastagi experimental farm, Karo regency, with type of the soil is andisol and altitude of 1,340 m asl. The research was beginning from February to May 2017. The design was used randomize block factorial with 2 replication. The first factor is the size of the seed (U1. small 25 g, U2. medium > 25 - 65 g and U3. large > 65 g). The second factor is the seed origin paclobutrazol use (P0. Control, P1. 7 WAP 250 ppm, P2. 7 WAP 500 ppm, P3. 8 WAP 250 ppm, P4. 8 WAP 500 ppm, P5. 9 WAP 250 ppm, P6. 9 WAP 500 ppm, P7. 10 WAP 250 ppm and P8. 10 WAP 500 ppm. The results showed that large seed size (> 65 g) was more important increasing vegetative growth of potato (plant height and canopy width, leaf area and number of tillers). The seed origin of paclobutrazole given at 8 WAP with dose 250 and 500 ppm have higher crop growth. The highest percentage of total seeds per plot is obtained by using medium size seed with use paclobutrazol 8 WAP 500 ppm (84.22%). Production of potato per plant and per plot was obtained by using medium seeds derived from the use of paclobutrazol 7 WAP 250 ppm (1.15 kg and 13.79 kg).